Digital Empowerment in the Design of Comprehensive Quality Assessment for Vocational Education Students - Xiao, Jianye; Liu, Long (Education Insights, 2026)
This study aims to explore effective pathways for leveraging digital technology to enhance the comprehensive quality assessment of vocational education students, establishing a scientific, objective, and rational evaluation system to promote their holistic development. In the contemporary educational landscape, this initiative holds significant importance for improving the overall quality and operational efficiency of vocational education, thereby advancing the broader education sector to meet modern industry demands. By systematically analyzing the definitions and classifications of emerging digital technologies—such as big data analytics, artificial intelligence, and cloud computing—alongside their current domestic and international educational applications, this research highlights both their distinct advantages and inherent challenges within vocational training environments. Furthermore, the study critically examines the persistent limitations of traditional evaluation methods, which often suffer from subjective biases, fragmented data collection, and a lack of real-time progress tracking. To address these critical gaps, the research meticulously identifies the core constituent elements of students' comprehensive qualities, encompassing academic proficiency, practical skills, and professional ethics. Based on these foundational findings, a robust, digital technology-based evaluation model tailored specifically for vocational education students is designed and proposed. This comprehensive framework outlines essential construction principles, the strategic selection of key technological tools, and the systematic development of standardized evaluation criteria. Ultimately, the proposed model provides a dynamic, data-driven approach to student assessment, ensuring a more accurate, transparent, and actionable measurement of student competencies, which will significantly contribute to the continuous improvement of vocational education paradigms.